Effect of interpass temperature on wire arc additive manufacturing using high-strength metal-cored wire - Zhai, Wengang (2022)
Wire arc additive manufacturing (WAAM) is suitable to fabricate large components because of its high deposition rate. In this study, a metal-cored low-alloy high-strength welding filler metal was used as feedstock. Single wall structures were prepared using the WAAM process with different interpass temperatures (150◦ C, 350◦ C, and 600◦ C). No obvious microstructure change was observed when the alloy was deposited with the interpass temperatures of 150◦ C and 350◦ C. Electron backscattered diffraction analysis shows that that no significant texture is developed in the samples. The yield strength tends to decrease with the increase in interpass temperature; however, the influence is insignificant. The highest ultimate tensile strength is found at the interpass temperature of 350◦ C. A higher interpass temperature can lead to a higher deposition rate because of the shorter waiting time for the cooling of the earlier deposited layer. It was found that the upper limit interpass temperature for WAAM of the low-alloy high-strength steel is 350◦ C. When a higher interpass temperature of 600◦ C was used, collapse of the deposited materials was observed.